2000
DOI: 10.1677/joe.0.1670439
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thyroid status regulates the expression of neuronal and astrocytic cytoskeletal proteins in the fetal brain

Abstract: Maternal thyroid hormone (TH) crosses the placenta and is postulated to regulate fetal brain development. However, TH-dependent stages of fetal brain development remain to be characterised. We have therefore compared the levels of several neuronal and glial cytoskeletal proteins in fetal brains from normal (N) and partially thyroidectomised (TX) rat dams by immunoblotting. Pregnancies were studied both before and after the onset of fetal TH secretion, which occurs at 17·5 days gestation (dg) in the rat.Materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
15
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
6
15
1
Order By: Relevance
“…59,60 Maternal glucocorticoid 61,62 and thyroid 63 hormones can cross the blood placental barrier and are essential for normal fetal neurodevelopment. 64,65 However, in humans, exposure of the fetus to excess glucocorticoids can have detrimental effects on fetal brain development 64,66 and hypothyroidism during pregnancy is associated with impaired cognitive and motor function in children. 67,68 Alternatively, the behavioral deficits observed in the adult offspring of rodents exposed to LPS during pregnancy could be the consequence of neurodevelopmental changes in the fetal brain resulting from LPS-dependent changes in the body temperature of the pregnant dam (i.e.…”
mentioning
confidence: 99%
“…59,60 Maternal glucocorticoid 61,62 and thyroid 63 hormones can cross the blood placental barrier and are essential for normal fetal neurodevelopment. 64,65 However, in humans, exposure of the fetus to excess glucocorticoids can have detrimental effects on fetal brain development 64,66 and hypothyroidism during pregnancy is associated with impaired cognitive and motor function in children. 67,68 Alternatively, the behavioral deficits observed in the adult offspring of rodents exposed to LPS during pregnancy could be the consequence of neurodevelopmental changes in the fetal brain resulting from LPS-dependent changes in the body temperature of the pregnant dam (i.e.…”
mentioning
confidence: 99%
“…The experimental groups on average showed a reduction in the thickness of layers and a reduction in the number of cells compared with the control group. The results of histomorphometry and cell counting in a study showed that the mother's affliction with hyperthyroid disease during pregnancy controlled cell multiplication in the external granular layer of the cerebellum and diminished the neural migration in the inner layer towards the side of the cortical area [23,24]. It seems that maternal hyperthyroidism also causes a delay to occur in embryonic brain growth, because the shortage of thyroid hormone in the embryotic period causes unnatural growth and a lack of distinction in cerebellum cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that maternal hypothyroidism can also disturb the ontogeny of these proteins in fetal brain, as well as that of -internexin (INX) -the earliest appearing neuronal specific intermediate filament (Sampson et al 2000). In the present study, we have investigated the hypothesis that chronic moderate maternal hyperthyroidism also impairs neuronal and astrocytic differentiation.…”
Section: Introductionmentioning
confidence: 92%
“…Early neuronal maturation, in particular, appears compromised (Evans et al 1999, Sampson et al 2000, with some deficits persisting in postnatal life (Porterfield & Hendrich 1991, Pickard et al 1997, Evans et al 1999.…”
Section: Introductionmentioning
confidence: 99%